Sexual Size Dimorphism On Some Penaeid Shrimp In Sudanese Red Sea - Ahmed, Mamduh Abdalla Osman (Journal of agricultural, environmental and veterinary sciences, 2017)
In Sudanese RedSea, Shrimp Morphometric relations were undertaken, on some penaeid species: Penaeus monodon, Penaeus indicus, Penaeus semisulcatus, Metapenaeus monoceros, Trachypenaeus curvirostris and Metapenaeus stebbingi. Females were larger than males in all studied species, the largest species was P. semisulcatus and the smallest one was Trachypenaeus curvirostris, which was 6g maximam weight during the study.  Table1. Some of body measurements Sexualdimorphism obtained in all morphometric measurements of P. semisulcatus and T. curvirostris. However, no sexualdimorphism in P. monodons’ morphometric measurements, in M. monoceros sexualdimorphism in length measurements and in P. indicus only in total length. The length weight relationship of studied shrimps differs according to the sex. Both sexes of T. curvirostris and P. semisulcatus shows sexual dimorphism in total length, carapace length and body weight, in P. monodon was no sexual dimorphism, P. indicus sexual dimorphism was in length measurements and in M. monoceros only in body weight.
Keywords: Sexual; Size; Dimorphism; Penaeid; Shrimp; Sudanese; Red Sea